2020
DOI: 10.1073/pnas.1914937117
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeling factor ARID2 suppresses hepatocellular carcinoma metastasis via DNMT1-Snail axis

Abstract: Recurrence and metastasis remain the major obstacles to successful treatment of hepatocellular carcinoma (HCC). Chromatin remodeling factor ARID2 is commonly mutated in HCC, indicating its important role in cancer development. However, its role in HCC metastasis is largely elusive. In this study, we find that ARID2 expression is significantly decreased in metastatic HCC tissues, showing negative correlation with pathological grade, organ metastasis and positive association with survival of HCC patients. ARID2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 30 publications
0
54
0
Order By: Relevance
“…As a subunit of the polybromo-associated BAF (PBAF) complex, ARID2 potentially interacts with epigenetic regulators and modulates gene transcription [ 28 ]. A recent study reported that DNMT1 was recruited as an epigenetic modulator by ARID2 to enhance the methylation of Snail promoter [ 29 ]. This observation promoted us to investigate the involvement of the ARID2-DNMT1 complex in the regulation of IFN-γ transcription.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a subunit of the polybromo-associated BAF (PBAF) complex, ARID2 potentially interacts with epigenetic regulators and modulates gene transcription [ 28 ]. A recent study reported that DNMT1 was recruited as an epigenetic modulator by ARID2 to enhance the methylation of Snail promoter [ 29 ]. This observation promoted us to investigate the involvement of the ARID2-DNMT1 complex in the regulation of IFN-γ transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Chromatin remodelling molecules often regulate gene expression by cooperating with epigenetic modulators, such as the E2F4-RBL2-HDAC1-BRM complex involved in proline-rich acidic protein 1 (PRAP1) transcriptional repression [ 50 ]. A recent study confirmed the recruitment of DNMT1 as an epigenetic modulator by ARID2 to enhance the methylation of gene promoter [ 29 ] that led us to investigate whether the ARID2-DNMT1 complex was also involved in the regulation of IFN-γ transcription. We verified the co-occupancy of ARID2 and DNMT1 at the same region of the IFN-γ promoter.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, because DNMT inhibitors can reverse the hypermethylated state at the promoters of epithelial markers such as E-cadherin, they also induce the activation of pro-metastatic genes. For instance, a most recent work indicates that DNMT1 can be recruited by a subunit of the chromatin remodeling complex to the Snail promoter and suppress its transcription, therefore downregulation of DNMT1 could also induce expression of EMT-TFs (Jiang et al, 2020). Consequently, targeting the DNA methylation readers like MBDs may provide a suitable alternative for the next generation of epigenetic therapies, and several studies have shown promising effects in terms of developing anticancer therapeutic strategies against the MBDs (Mahmood and Rabbani, 2019).…”
Section: Epithelial-mesenchymal Transition and Dna Methylationmentioning
confidence: 99%
“…Duan et al suggested a mechanism through which ARID2 controls cell proliferation by regulating the expression of cell cycle components. More recently, Jiang et al described ARID2 downregulation in metastatic HCC, in association with poor prognoses [ 74 ]. ARID2-Kd was associated with increased migration and invasion in HCC cell lines whereas ARID2 over-expression in HCC cell lines and their related metastatic derivative inhibited invasion and migration.…”
Section: Arid2 In Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%